2021
DOI: 10.3390/s21093007
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis Prototypic Polystyrene Particle Synchronization toward Alive Keratinocyte Cells for Rapid Chronic Wound Healing

Abstract: Diabetes patients are at risk of having chronic wounds, which would take months to years to resolve naturally. Chronic wounds can be countered using the electrical stimulation technique (EST) by dielectrophoresis (DEP), which is label-free, highly sensitive, and selective for particle trajectory. In this study, we focus on the validation of polystyrene particles of 3.2 and 4.8 μm to predict the behavior of keratinocytes to estimate their crossover frequency (fXO) using the DEP force (FDEP) for particle manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…However, the electric field gradient remained unchanged to the increase of applied frequency. Although the frequency has not contributed to the electric field gradient but note that it is still an important factor that influence the particle, as the particle DEP response is highly dependent on applied frequency and which is governed by the equation (2) and equation ( 3) 11 . This result has shown that the applied voltage has a substantial influence on the electric field gradient, however the applied frequency will have no effect on the electric field gradient.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electric field gradient remained unchanged to the increase of applied frequency. Although the frequency has not contributed to the electric field gradient but note that it is still an important factor that influence the particle, as the particle DEP response is highly dependent on applied frequency and which is governed by the equation (2) and equation ( 3) 11 . This result has shown that the applied voltage has a substantial influence on the electric field gradient, however the applied frequency will have no effect on the electric field gradient.…”
Section: Resultsmentioning
confidence: 99%
“…TAMA work led to the identification of a tapered side wall between 60 and 70 degrees for the generation of a more uniform electric field from two spots at top and bottom edges of the tapered microelectrodes [161]. Refinement of the TAMA work concluded that 65 degrees was the best reading in TAMA to generate dielectrophoretic force for lateral and vertical manipulation of particle manipulation as shown in Figure 5b [164]. A DEP study on keratinocytes using "MyDEP" software showed that the DEP response of keratinocytes was successfully simulated by using polystyrene particles [164].…”
Section: Dielectrophoresis (Dep)mentioning
confidence: 99%
“…Refinement of the TAMA work concluded that 65 degrees was the best reading in TAMA to generate dielectrophoretic force for lateral and vertical manipulation of particle manipulation as shown in Figure 5b [164]. A DEP study on keratinocytes using "MyDEP" software showed that the DEP response of keratinocytes was successfully simulated by using polystyrene particles [164]. This is of interest, as DEP targeted specific cells and hence, the mobilisation of keratinocytes in an appropriate direction, and the plane will make re-epithelisation possible, especially in the case of a chronic wound with sufficient granulation but slow or no opposing wound edges.…”
Section: Dielectrophoresis (Dep)mentioning
confidence: 99%
“…A TAMA consists of an aluminum microelectrode array on a silicon substrate and is fabricated based on the CMOS processing technique [ 27 , 28 ]. Based on the investigation from our previous studies, the F DEP produced by this microelectrode produced a higher gradient non-uniform electrical field from the top and bottom edges of the microelectrode [ 29 , 30 ]. It managed to separate and isolate more than one type of particle depending on the F DEP acting on the particles by adjusting the frequency of the electrical field.…”
Section: Introductionmentioning
confidence: 99%